The Concept of al-Bay’ in The Qur’an Perspective with The Maudu’i Methodological Approach Konsep al-Bay’ dalam Perspektif al-Qur’an dengan Kajian Metode Maudu’i - Syaichoni, Ahmad; Rifki Sahara (Aqwal: Journal of Qur'an and Hadis Studies, 2022)
Business transactions in the modern era require the use of technology and information. The sale and purchase contract is a familiar type of business transaction. Buying and selling has been practiced since ancient times. Nevertheless, modern development is taking place. All human transactions are governed by the Qur'an. Buying (al-bay') is one of the studies discussed in the Qur'an. The meaning and definition of al-bay' in the Qur'an differ from one letter to the next. This research reveals how the Qur'an views the concept of al-bay' in general. This study employed a maudu>'i> interpretation study approach in its library research. This maudu>'i interpretation study is used to explore data about al-bay' then explained based on the Koran's interpretation. The findings indicate that the word al-bay' in the Koran has two meanings. To begin, al-bay' discusses economic issues, particularly purchasing and selling transactions. So al-bay' is always associated with profit in worldly affairs. This is the meaning of al-bay', which is widely debated among Islamic economists. While eating al-bay', the second discusses the issue of ukhrawi life and faith. The meaning that emerges as a result of the modern world's conditions is that al-bay' is associated with the economic field. The truth is that economic conditions are rapidly changing, and one example is online buying transactions.